2022
DOI: 10.3390/nu14020260
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Taxa Abundance and Diversity in Inflammatory Bowel Disease Patients: An Analysis including Covariates and Confounders

Abstract: Intestinal dysbiosis has been widely documented in inflammatory bowel diseases (IBDs) and is thought to influence the onset and perpetuation of gut inflammation. However, it remains unclear whether such bacterial changes rely in part on the modification of an IBD-associated lifestyle (e.g., smoking and physical activity) and diet (e.g., rich in dairy products, cereals, meat and vegetables). In this study, we investigated the impact of these habits, which we defined as confounders and covariates, on the modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 56 publications
5
21
0
Order By: Relevance
“…Additionally, in a murine colitis model, consumption of a choline-deficient diet led to a decrease in relative abundance of Erysipelotrichaceae [ 72 ]. Moreover, Bifidobacterium appears to increase in abundance during active IBD and has been reported as a predominant genus in the microbiome of Taiwanese IBD patients [ 73 , 74 , 75 , 76 ]. On the other hand, administration of Bifidobacterium longum suppressed development of preneoplastic lesions in mice and appeared to induce expression of tumor-suppressing microRNAs [ 77 ], whereas Bifidobacterium infantis conferred protection against DSS-induced colitis and abnormal immune signaling [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in a murine colitis model, consumption of a choline-deficient diet led to a decrease in relative abundance of Erysipelotrichaceae [ 72 ]. Moreover, Bifidobacterium appears to increase in abundance during active IBD and has been reported as a predominant genus in the microbiome of Taiwanese IBD patients [ 73 , 74 , 75 , 76 ]. On the other hand, administration of Bifidobacterium longum suppressed development of preneoplastic lesions in mice and appeared to induce expression of tumor-suppressing microRNAs [ 77 ], whereas Bifidobacterium infantis conferred protection against DSS-induced colitis and abnormal immune signaling [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although not supported by clear scientific evidence, maintaining a low-fiber diet after an episode of acute diverticulitis may decrease intestinal bacterial diversity, a phenomenon already observed in IBD cases. 11 Together with modifications linked to aging, these changes may therefore represent a perfect background for the persistence of an altered immune response. Finally, a significant role may be played by the Akkermansia muciniphila species.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, Desulfovibrionaceae was considered to be a type of bacteria that posed health risk due to its positive correlation with intestinal and systematic inflammation (20,21). Moreover, clinical data suggested that the presence of Desulfovibrionaceae was associated with chronic periodontitis, cell death, and inflammatory bowel diseases (22)(23)(24). With regard to Lactobacillus, it has been generally proved to play an essential role in maintaining homeostasis.…”
Section: Discussionmentioning
confidence: 99%